Metabolic, Cardiovascular, and Cerebrovascular Outcomes in Growth Hormone-Deficient Subjects with Previous Cushing’s Disease or Non-Functioning Pituitary Adenoma - Webb, Susan M.; Mo, Daojun; Lamberts, Steven W. J.; Melmed, Shlomo; Cavagnini, Francesco; Pecori Giraldi, Francesca; Strasburger, Christian J.; Zimmermann, Alan G.; Woodmansee, Whitney W. (The journal of clinical endocrinology and metabolism, 2010)
Context: Previous exposure to hypercortisolism due to Cushing’s disease (CD) may adversely affect long-term metabolic and cardiovascular outcomes. In particular, metabolic and cardiovascular outcomes of patients with previous CD who require GH replacement have not been fully established. Objective: The aim of the study was to compare the prevalence and incidence of metabolic syndrome (Adult Treatment Panel III criteria), diabetes mellitus, cardiovascular disease, and cerebrovascular disease in GH-treated subjects with previous CD with GH-treated subjects with previous nonfunctioning pituitary adenoma (NFPA). Design: We conducted post hoc analysis of the observational Hypopituitary Control and Complications Study conducted at 362 international centers (1995–2006). Subjects: We studied adult-onset GH-deficient subjects with previous CD (n = 160) or NFPA (n = 879). All subjects received GH replacement therapy and were GH naive at enrollment. Multiple pituitary deficits were prevalent in both groups. Main Outcome Measures: We measured the prevalence and incidence of metabolic syndrome, diabetes mellitus, cardiovascular disease, and cerebrovascular disease at baseline and at 3 yr, standardized for age and sex differences between groups. Results: Compared with subjects with previous NFPA, subjects with previous CD had a significantly greater 3-yr incidence of metabolic syndrome (CD, 23.4%; NFPA, 9.2%; P = 0.01), baseline (CD, 6.3%; NFPA, 2.2%; P < 0.01) and 3-yr (CD, 7.6%; NFPA, 3.9%; P = 0.04) prevalence of cardiovascular disease, and baseline (CD, 6.4%; NFPA, 1.8%; P = 0.03) and 3-yr (CD, 10.2%; NFPA, 2.9%; P = 0.01) prevalence of cerebrovascular disease. Conclusions: Previous hypercortisolism may predispose GH-treated, GH-deficient subjects with prior CD to an increased risk of metabolic syndrome, cardiovascular disease, and cerebrovascular disease.